The Darker the Skin, the Greater the Disparity? Why a Reliance on Visible Injuries Fosters Health, Legal, and Racial Disparities in Domestic Violence Complaints Involving Strangulation - Brady, Patrick Q. (Journal of interpersonal violence, 2023)
The reliance on external injuries for justice is misguided given that assault injuries may be less visible among victims of color due to increased melanin in the skin. To date, however, less is known whether racial/ethnic disparities extend to officers’ identification of signs of nonfatal strangulation (NFS). The current study estimates the extent of NFS indicators identified by officers who completed a standardized strangulation assessment in 133 family violence complaints. Breathing difficulties were the most common symptoms identified by officers (98%), followed by external signs (89%), and symptoms of impeded blood circulation (87%). Compared to cases involving White/Asian survivors, officers were less likely to identify external injuries on Black survivors’ neck, chin, and chest/shoulders. While racial/ethnic differences did not emerge for symptoms of disrupted airflow, Hispanic survivors were twice as likely to report losing control of bodily functions. Implications for policy and practice are discussed.